STAGING HERITAGE: UNVEILING THE SOCIO-POLITICAL ROLE OF FOLK ARTS IN INDIA - Deleep D L (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Theatre serves as a potent medium for conveying ideas and providing entertainment through creative experiences. India boasts a long and rich theatrical tradition, with its origins deeply intertwined with ancient rituals. The foundational text of Indian theatre, Bharata's Natya Shastra, attributes a divine genesis to this art form, linking it to the natyaveda. Initially, Indian theatre emerged as a narrative art form that integrated recitation, singing, and dancing as essential components. Over time, it has assimilated various forms of literature and fine arts into its physical presentations. Indian theatre can be categorized into three distinct phases. The second phase was characterized by oral traditions, during which folk theatre flourished across different regions and languages. This vibrant folk theatre emerged forcefully, reflecting the diverse cultural narratives and practices inherent in various Indian communities.